AN ANALYSIS OF INDONESIAN MORAL VALUES FOUND IN THE SONG LYRICS FORGIVE ME ALBUM BY MAHER ZAIN - Lutfy Fajar Hudayah (Universitas Ahmad Dahlan)
Moral values are standard accepted principles of life. It is concerned with the principles of right and wrong behavior and the goodness or badness of human characters. Moral values from a subset of the set of all values, and value simply consist of the things that some people values. The purpose of this study were as follows (1) to find out the Indonesian moral value in song lyrics album by Maher Zain, (2) to find out the kinds of the moral values in the song lyrics album by Maher Zain and (3) to find out the most frequent moral values in the song lyrics album by Maher Zain. Subject in this study are song lyrics that consider and containing moral values. This study was qualitative descriptive because this study is aim to make systematic, factual, accurate description of the moral values in the song lyrics forgive me album. The data was analyzed systematically based on the data Moleong (2009: 6) who state that qualitative research is a kind of research carried out to understand the phenomena that occur in research subject such as musical note; intonation and meaning of song lyrics by describe it in words and using various scientific method. The result of this analysis is shown eleven moral values are found in Forgive Me album by Maher Zain songs. The similarities Indonesian moral values wih the moral values found n Maher Zain songs, and the moral values most frequent in forgive me album by Maher Zain song. The findings of the moral values in Forgive me album by Maher Zain are eleven. There are religiosity, love affection, loyalty, sincerity, thankfulness, steadfastness, humbleness, peace loving, brotherhood, respecting other, and optimism. The Indonesian moral values found in the song lyrics album are religiosity, communicative, and peace-loving. And the moral values most frequent in the song lyrics album are religiosity, love affection and loyalty.